Peningkatan Hasil Belajar PAI dengan Metode Diskusi - Yenti, Elva (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Grade VI students at SDN 09 Simpang Utara in Islamic Education (PAI) by implementing the discussion method. The main issue identified was the low level of student engagement in learning, which negatively impacted their understanding of the material and internalization of religious values. The discussion method was chosen as it promotes active student participation, enhances critical thinking skills, and facilitates a deeper understanding of the subject. The study focused on students' learning outcomes across cognitive, affective, and psychomotor domains, utilizing small group discussions guided by teachers. The results indicate that implementing the discussion method significantly improved students' learning outcomes in PAI. Through this approach, students became more active, motivated, and capable of applying Islamic values in their daily lives.